1998
DOI: 10.1016/s0022-5223(98)70176-x
|View full text |Cite
|
Sign up to set email alerts
|

Paraplegia after surgery of the thoracic esophagus

Abstract: Paraplegia after thoracic surgery is an uncommon complication, [1][2][3][4] and it is even more uncommon after surgery of the thoracic esophagus. Herein we describe 2 cases that occurred in our experience.Clinical summaries CASE 1. A 72-year-old man was admitted for the treatment of worsening dysphagia. Barium swallow and esophagogastroscopy revealed a mass 31 cm from the incisors, and the biopsy results showed squamous carcinoma. There was no evidence of locoregional spread or metastases at endosonography and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Finally, esophageal surgery is not without potentially serious complications. Mineo et al 499 describe paraplegia and Levitt et al 500 describe intraoperative cardiac tamponade, successfully treated.…”
Section: Investigating the Esophagus (For Manometry See Esophageal Mmentioning
confidence: 99%
“…Finally, esophageal surgery is not without potentially serious complications. Mineo et al 499 describe paraplegia and Levitt et al 500 describe intraoperative cardiac tamponade, successfully treated.…”
Section: Investigating the Esophagus (For Manometry See Esophageal Mmentioning
confidence: 99%
“…Neurologic deficits resulting from spinal cord ischemia are very rare complications of esophagectomy and are probably often not diagnosed because of an unawareness of this entity 1 . They present with a pattern of neurologic deficits dependent upon the occluded vessel.…”
Section: Introductionmentioning
confidence: 99%
“…Neurologic de®cits resulting from spinal cord ischemia are very rare complications of esophagectomy and are probably often not diagnosed because of an unawareness of this entity. 1 They present with a pattern of neurologic de®cits dependent upon the occluded vessel. The anterior spinal artery syndrome (ASAS) as a sequela of occlusion of the anterior spinal artery is the most frequently described entity of this group.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the world literature since 1966 showed that only 4 such cases have been reported. [1][2][3] We add a fifth case, that of a patient who was referred to our institution for follow-up after resection of adenocarcinoma of the…”
mentioning
confidence: 99%